Dekontruksi Citra Muslim di Eropa:: Pendekatan Moral Humanis Tariq Ramadan - Erinda Rizka Khaolina; Ahmad Anas Fajarul (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This article discusses the efforts to deconstruct the negative image of the Muslim community in Europe through a humanist moral approach developed by a contemporary Muslim intellectual, Tariq Ramadan. In the context of increasing Islamophobia and stereotypes against Muslims after global events such as the September 11 attacks (9/11) and terrorist attacks in Europe, Ramadan offers a new paradigm that emphasizes the importance of integration without losing Islamic identity. The moral approach he initiated is based on universal Islamic values such as justice, compassion, social responsibility, and openness to intercultural dialogue. Through this framework, the article examines how Ramadan encourages Muslims to appear as active and constructive citizens in a pluralist European society. In addition, Ramadan's criticism of both religious fundamentalism and radical secularism is also discussed, which often closes off space for healthy religious expression. Thus, this article shows how Islamic humanist ethics can be a bridge to build a more harmonious relationship between Muslims and European society at large.